Attentional Capture From Inside vs. Outside the Attentional Focus - Manini, Greta; Botta, Fabiano; Martín-Arévalo, Elisa; Ferrari, Vera; Lupiáñez, Juan (Frontiers in Psychology, 2021)
In the present study, we jointly addressed empirically and theoretically – for the first time – two main theories: Lavie’s perceptual load theory and Gaspelin and colleagues’ attentional dwelling hypothesis. These theories explain in different ways the modulation of perceptual load/task difficulty over attentional capture by irrelevant distractors, and lead to the observation of opposite results with similar manipulations. We hypothesized that these opposite results may critically depend on the distractor type used by the two experimental procedures (i.e., distractors inside vs. outside the attentional focus, which could be respectively considered as potentially relevant vs. completely irrelevant to the main task). Across a series of experiments, we compared both theories within the same paradigm by manipulating both the perceptual load/task difficulty and the distractor type. Results were strongly consistent, suggesting that the influence of task demands on attentional capture varies as a function of distractor type: while the interference from (relevant) distractors presented inside the attentional focus was consistently higher for high vs. low load conditions, there was no modulation by (irrelevant) distractors presented outside the attentional focus. Moreover, we critically analyzed the theoretical conceptualization of interference by both theories, disentangling important outcomes for the dwelling hypothesis. Our results provide specific insight into new aspects in attentional capture, which could critically redefine these two predominant theories.